2017
DOI: 10.7759/cureus.1199
|View full text |Cite
|
Sign up to set email alerts
|

Learning Microvascular Anastomosis in Low Socioeconomic Vascular Models During Residency

Abstract: Microvascular anastomosis procedure has become an essential practice for the management of most neurovascular diseases. Increasing use of neurosurgical techniques necessitates intensive laboratory training in microsurgery.Umbilical artery is used for quantifiable representation to set up microvascular anastomosis model for the beginners. These arteries are found to be between 4 and 5 mm in diameter. Chicken wings are set up as second anastomosis model. Five to six centimeter long brachial artery extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…One of the features of the models in anastomosis training should be the monetary burden [16]. The desktop microscope was used in previous studies instead of an operating microscope, and no problem was reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…One of the features of the models in anastomosis training should be the monetary burden [16]. The desktop microscope was used in previous studies instead of an operating microscope, and no problem was reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…In general, they are divided into low-and high-fidelity and their use is dependent on the various levels of microsurgical proficiency of trainees. Four basic categories of models are used, including inanimate prosthetic materials, cadaveric animal tissue, cadaveric human tissue and live animals [1,[4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation with the use of live animal models (rat aorta, femoral or carotid artery) is considered the gold standard for advanced microsurgical training, however this is associated with several obvious disadvantages, including lesser accessibility, costs and ethical issues [1]. Moreover, there isn't convincing evidence that this model is necessary as an intermediate step between the animal cadaveric model and clinical microsurgical practice [1,[4][5][6][7]. Non-living models including chicken vessels or soft-fixed human vessels may actually be better training platforms than the live rat model, where the vessel calibre, wall thickness and tissue handling more closely simulate human blood vessels in vivo [8].…”
Section: Simulation Modelsmentioning
confidence: 99%
“…2 However, due to the high cost of animals, preparation difficulty, and need to sacrifice after use, several studies suggested that nonanimal model uses, such as silicone tube, rubber glove, gauze, fresh leaf, or nonliving specimens, such as chicken wings or thighs, cold stored vessels, pig leg, avulsed skin, placenta vessels, are all suitable for practicing microsurgical skills before proceeding to practice in living specimens to test thrombogenicity and real patency rates. [3][4][5][6][7] The second approach is to practice with microsuture. Typical suture size for microanastomosis is 8/0 (diameter 45 µm) to 10/0 (diameter 20 µm) depending on patient vessel size).…”
Section: Discussionmentioning
confidence: 99%